The opportunity cost of spiny dogfish (Squalus acanthias) bycatch in a ling (Genypterus blacodes) longline fishery. (July 2019) - Howard, Sunkita; Kahui, Viktoria; Rock, Jenny
Abstract: The economic impact of spiny dogfish in a New Zealand ling longline fishery was assessed for the purpose of guiding early-stage bycatch reduction device (BRD) development. Ling fishermen describe being "dogged out", events where high dogfish catch per unit effort (CPUE) is assumed to cause low ling CPUE. Overall, fisheries observer data showed a significant, weak positive relationship between these species' CPUE, which was expected given their spatio-temporal co-occurrence. On fishing lines in the upper quartile for spiny dogfish CPUE (193 dogfish per thousand hooks, a proxy for large "dogged out" events), there was a significant, moderate, negative relationship between dogfish and ling CPUE, providing support for the view of ling fishermen. An opportunity cost for these events was estimated where the value of ling 'lost' was approximated by using the ratio of ling to dogfish per line. These lines caught almost 16, 000 dogfish, which equated to just over 6000 lost ling worth 75, 000 NZD. This cost was adjusted to all hooks in the dataset, as large dogfish events cannot be discerned in advance, equating to 23 cents per hook, per fishing event. A per-hook BRD that eliminates this opportunity cost must reduce dogfish CPUE to below the "dogged out" threshold and cost <23 cents per unit, per fishing event. A 23 cent, single-use BRD would meet this standard, as would a $23 BRD that can be used 100 times. This approach could be used to establish BRD price and performance standards for any bycatch problem that reduces fishing efficiency. Highlights: Skippers assume spiny dogfish bycatch reduces ling catch rates. On lines with large spiny dogfish catches, 0.4 ling are lost for every dogfish caught. The opportunity cost of dogfish bycatch in lost ling is 0.23 NZD per hook. A cost-neutral BRD would eliminate lines with large dogfish catches and cost <23 cents per unit/use.